Community risk perception and health-seeking behavior in the era of COVID-19 among adult residents of Harari regional state, eastern Ethiopia. (July 2021) - Eyeberu, Addis; Mengistu, Dechasa Adare; Negash, Belay; Alemu, Addisu; Abate, Degu; Raru, Temam Beshir; Wayessa, Alemayehu Deressa; Debela, Adera; Bahiru, Nebiyu; Heluf, Helina; Kure, Mohammed Abdurke; Abdu, Ahmedmenewer; et al.
Background: COVID-19 brought significant challenges to public health. It changed the view of global health and safety, trust in the healthcare system, and clients' willingness to seek healthcare. To contain the course of the COVID-19 pandemic and its detrimental effects, understanding peoples' health behavior, especially healthcare-seeking, and determining the community risk perception is very important. Thus, this study aimed to determine the health-seeking behavior, community's risk perception to COVID-19 pandemics, and factors influencing the community risk perception in Harari regional state, Ethiopia. Methods: Community-based cross-sectional study was conducted from 5 to 30 February 2021. A total of 1320 adult (>18 years) participants were selected using systematic random sampling. The data were collected using an online kobo collect toolbox and analyzed using descriptive statistical tests. Chi-square test and multiple binary logistic regression were applied to examine the difference between variables. A p -value < 0.05 was considered to be of statistical significance. Results: The study included 1296 respondents >18 years old. The overall prevalence of willingness to seek healthcare in the study area was 35.6% (95% CI: 33%–38.3.0%). The mean cumulative score of risk perception was 30.5 (SD ± 7.25) with the minimum and maximum score of 13 and 63, respectively. A total of 656 (50.6%) of the participants had low-risk perceptions concerning COVID-19. The study found a statistically significant association between risk perception and sociodemographic characteristics (age, educational status, and income), and knowledge of the respondents. Conclusion: The overall prevalence of willingness to seek healthcare was 35.6%. Healthcare intervention aimed to contain the COVID-19 pandemic should consider the factors associated with the study area. Similarly, the study found a low-risk perception among the community that needs critical action to manage the COVID-19 pandemic and to protect the community as a whole. Thus, it is necessary to improve community risk perception through health education.